Exhaust air from a farrowing house used to heat a greenhouse - Greig, J.K.; Spillman, C.K.; Koch, B.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Exhaust air from the Kansas State University swine farrowing house provides most of the heat needed in a greenhouse adjacent to it. The air apparently is not toxic to any of the vegetable plants tested. Tomato plants in the exhaust-air-heated greenhouse have grown faster and bigger, come into yield sooner, and produced several times more tomatoes than have plants grown in the control greenhouse heated by propane.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Exhaust air; Farrowing house; Greenhouse